Featured Answer

Asked on

Use the inverse A^(-1) in (a) to solve.... have answer already don't know how to obtain.?

Use the inverse A^(-1) in (a) to solve Ax.





the inverse for (a) is; (**dots just for spacing)




answer should be




can someone explain how this answer is obtained. 10pts for explanation

Answers (3)

t4zr0nmtaa profile image
06rw9cwhaa profile image

The numbers you have given do not agree with the answer you gave.

This method of solution is based on the fact that if

AX = B where A is the matrix of coefficients and B is the matrix of constants, then

A^-1AX = A^-1B and A^-1A = I where I is the identity matrix so

X = A^-1B

The numbers you have given for A^-1 and B yield x = 5, y = 1/2, and z = 0.

jq3we5gyaa profile image

Just multiply Ax by A^-1 on the left.

Reference: Verified on TI-84 calculator.